Design of Broadband GaN 0.15μm RF Switches and X-band Reconfigurable Impedance Tuner - Khan, Iftekhar (Université d'Ottawa / University of Ottawa, 2016)
Radio-frequency (RF) switches are widely used in electrical systems, telecommunications, and wireless applications. In RF systems, it is often desirable to change the signal path effectively, by us-ing couplers, duplexers, and RF switches for signal division and combining. Typically, in modern RF systems, the RF switch is mostly capitalized in order to reduce the RF footprint but with efficient switch characteristics. A simple method to reduce transceiver space requirement is to integrate RF switches with the frontend module on a single chip. Recent advances in Gallium Nitride (GaN) technology allows RF designers to design faster, smaller, and efficient components using this technology. With high data rates in demand for wireless communication systems, wideband characteristics are needed in modern systems [1]. Therefore, it is desirable to design wideband circuits; such as, mixers, amplifiers, and switches. In this work, a comprehensive study of NRC GaN150 HEMT is conducted to design broadband RF switches. Single pole and double pole switch topologies operating at 1-12 GHz are designed to evaluate GaN 0.15μm RF switches. The main objectives were to design compact sized switches, while having high power handling, low insertion loss, high isolation and high return loss. Additionally, a transmit-receive switch is designed for integration into a frontend module and further fabricated to operate at 10 GHz. There are many applications of RF switches in an RF transceiver, one of which is an impedance tuner. Impedance tuner are attractive for many applications where mobile devices are used for wireless communications. As mobile technology continues to evolve, they are designed to be com-pact, leaving minimal space for the antenna. Consequently, the radiating element is often electrically small and sensitive to near-field coupling requiring tuning. Matching networks aim to tune matching conditions; for example, loading effects due to human hand [2]. For such situations, specialized matching networks can be designed to account for specific loading environmental effects. However, for mobile systems, the environment is unknown; thereby, yielding unpredictable antenna loading, especially for electrically small antennas that have rapidly changing real and imaginary impedance. As a result, it is necessary to design a reconfigurable impedance-matching network to account for possible load impedances. In this work, a 16-bit reconfigurable impedance tuner design comprising of passive microwave components and NRC GaN 0.15μm FET operating at X-band is presented to evaluate its performance for integration with the frontend module on a single chip to reduce cost and increase efficiency of the system.
Keywords: RF; GaN; RF Switch; MMIC; Impedance Tuner; SPDT; DPDT; SPST; Frontend Module